New approaches for H2-driven NADH regeneration using carbon supports - Zhao, X (2024)
The selective reduction of ketones to enantiomerically pure products, such as alcohols or amines, plays an important role in synthesising active pharmaceutical ingredients (APIs). Particularly, enzymatic approaches are very useful for such reductions, offering high enantioselectivity under relatively mild operating conditions. However, a key limitation of utilising enzymes for selective reduction of ketones is the requirement of expensive cofactors, usually in the form of NADH or NADPH. Therefore, an efficient cofactor recycling system is a prerequisite to exploit redox enzymes in these synthetic pathways.